PENGARUH EDUKASI HIGIENE SANITASI MAKANAN MELALUI MEDIA GROUP WHATSAPP TERHADAP PENGETAHUAN,SIKAP DAN PERILAKU PENJAMAH MAKANAN DI LAPANGAN KARANG KOTAGEDE YOGYAKARTA - Delima Citra Dewi Gunawan; Fera Nofiartika; Farah Ajeng Nirasari; Bayu Prasetiyo (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
The Effect of Food Hygiene Sanitation with Whatsapp Group Media on Knowledge, Attitude and behaviour on Food Handlers in Karang Field Kotagede YogyakartaBackground: Contaminated food is often made and sold by street hawkers due to poor hygiene and sanitation standards. Food sanitation hygiene behavior can be improved by means of whatsapp media education. The whatsapp application is one of the applications with the highest number of usage in the world.Objective: To determine the effect of food sanitation hygiene education through the whatsapp group media on food handler behavior. Methods: This research type is a quasi experiment with one group pre test post test design. The research respondents were 21 food handlers who were determined by purposive sampling. Data collection using an observational checklist sheet. Data were analyzed using paired sample t-test. Results: Based on the paired sample t-test, the significance value (sig) of the behavior level was 0.358 (p> 0.05). The result of the average score of behavior before the intervention (pre test) given food sanitation hygiene education was 16.81, including the moderate category (67.05%). The average result of the behavior score before the intervention after (post test) given food sanitation hygiene was 16.95, including the moderate category (67.81%). Conclusion: There was no difference in behavior before and after food hygiene education was carried out using the WhatsApp group media.